FACTORS AFFECTING PRESERVICE ENGLISH TEACHERS' TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) - Endang Darsih; Vina Agustiana; Wulan Rahmatunisa; Agie Hanggara (Indonesian Journal of Learning and Instruction, 2024)
The integration of technology into teaching is critical for preparing educators to meet the demands of 21st-century classrooms, particularly in English as a Foreign Language (EFL) contexts. This study investigates the factors influencing the development of Technological Pedagogical Content Knowledge (TPACK) among preservice English teachers, addressing gaps in existing research that often overlooks this group. Using a mixed-methods approach, quantitative data from 30 participants were collected via a validated TPACK questionnaire, while qualitative insights were gathered through in-depth interviews with a purposive sample of 10 preservice teachers. The findings highlight significant variability in TPACK levels, with technological knowledge emerging as the most challenging domain. Four key factors—access to technological resources, mentorship from experienced teachers, prior experience with technology, and professional development opportunities—were identified as crucial for TPACK development. Limited access to resources and insufficient training were common barriers, whereas mentorship and prior exposure to technology positively influenced confidence and adaptability. The study concludes that tailored interventions, such as resource provision, mentorship programs, and technology-focused training workshops, are essential for enhancing preservice teachers' TPACK proficiency. Educational institutions must prioritize these measures to equip future educators with the skills needed for effective technology integration. Further research is recommended to explore these factors across diverse educational contexts to inform comprehensive strategies for improving teacher education programs.Keywords: TPACK; preservice teachers; EFL, technology integration; mentorship; teacher training; professional development